Nurse's perceptions of physiotherapists in critical care team: Report of a qualitative study - Gupte, Pranati; Swaminathan, Narasimman (Wolters Kluwer -Medknow, 2016)
Background: Interprofessional relationship plays a major role in effective patient care. Specialized units such as critical care require multidisciplinary care where perception about every members role may affect the delivery of patient care. The objective of this study was to find out nurses’ perceptions of the role of physiotherapists in the critical care team. Methods: Qualitative study by using semi‑structured interview was conducted among the qualified nurses working in the Intensive Care Unit of a tertiary care hospital. The interview consisted of 19 questions divided into 3 sections. Interviews were audio recorded and transcribed. In‑depth content analysis was carried out to identify major themes in relation to the research question. Results: Analysis identified five major issues which included role and image of a physiotherapist, effectiveness of treatment, communications, teamwork, and interprofessional relations. Physiotherapists were perceived to be an important member of the critical team with the role of mobilizing the patients. The respondents admitted that there existed limitations in interprofessional relationship. Conclusion: Nurses perceived the role of physiotherapist in the critical care unit as an integral part and agreed on the need for inclusion of therapist multidisciplinary critical care team.